The role of the principal in strengthening character education in elementary school - Fajri, Nurul; Dafit, Febrina (Indonesian Values and Character Education Journal, 2022)
The role of the principal is very important in strengthening character education because the principal, as a policy maker, can accommodate all student needs related to character education and a leader who can encourage all teachers and employees to become good character models for all students will greatly determine the success of character education can be implemented. This study aimed to analyze the role of school principals in strengthening character education. This research is a type of descriptive qualitative research. The subjects of this study amounted to 1 principal and 6 class teachers. The methods used for data collection are observation, interviews, and document review. The instruments used to collect data are interview sheets and observation sheets. The results showed that based on the results of interviews and observations, the role of the principal in strengthening character education is very large and can affect the attitudes and personalities of children at school. Guidance, motivation, and facilities provided by students are very much needed to get more motivation in strengthening character education. This research implies that school principals can carry out their duties according to their role in strengthening character education.